Being fair in an unfair world: The deleterious effect on self-esteem. (April 2021) - Collins, Erynn; Strelan, Peter
Abstract: The concept of fairness is deeply ingrained in human behavior, so much so that people strive to act fairly. However, the world itself is not a fair place. In this study we asked, what is the effect on self-perception—specifically, self-esteem—when a person acts fairly in a world that they believe is not fair? We addressed this question in a sample of N  = 198 Australian undergraduates. We found that individuals who value fairness but score low on just world beliefs for the self (BJW-self) tend to indicate reduced self-esteem. In contrast, this effect does not occur when individuals who value fairness score high on BJW-self. We also tested and found support for two secondary hypotheses, that fairness has an indirect effect on self-esteem through intrapersonal consistency, and BJW-self has an indirect effect on self-esteem through personal control. Highlights: Self-esteem suffers among those who endorse fairness in an unfair world. Intrapersonal consistency positively mediates between fairness and self-esteem. Control positively mediates between BJW-self and self-esteem.